Psychophysiological stress markers during preseason among elite female soccer players - Botelho, R.; Abad, C. C. C.; Spadari, R. C.; Winckler, C.; Garcia, M. C.; Guerra, R. L. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to investigate changes and correlations between mood states and various physiological stress markers after a 7-week preseason period among elite female soccer players. Twenty-four elite female soccer players participated in this study (26.4 ± 3.7 years). Their internal training load, mood states, day and evening salivary testosterone and cortisol concentrations, blood creatine kinase concentration (CK), and heart rate variability (HRV) were assessed during the first week of preseason (PRE), and again 7 weeks after a systematic training period (END). After the preseason, there were significant increases in subject negative mood scales (p = 0.03; Effect Size [ES] > 0.60), total mood scores (p = 0.01; QI = 100/0/0; ES = 1.32), day and evening testosterone and cortisol concentrations (p = 0.03; ES > 0.54), and CK concentrations (p = 0.01; QI = 100/0/0; ES = 1.54). Correlations were found between cortisol and tension (r = 0.53 and 0.60; p = 0.02), cortisol and confusion (r = 0.75; p = 0.01), and cortisol and the LF/HF index of HRV (r = -0.52; p = 0.04). Mood states (except vigor), salivary testosterone, and cortisol concentrations, as well as CK, showed significant changes after a 7-week systematic training system. The cortisol was the factor most highly related to various mood states (including tension and confusion), and with the HRV indices. Coaches and researchers can use these data to design, monitor, and control soccer training programs, in particular throughout the preseason period.